2012
DOI: 10.1007/s00405-012-2124-2
|View full text |Cite
|
Sign up to set email alerts
|

Smell in cystic fibrosis

Abstract: In cystic fibrosis (CF), the most frequent life threatening inherited disease in Caucasians, sinonasal mucosa is regularly affected by defective mucociliary clearance. This facilitates pathogen colonization into CF airways and causes frequent symptoms of rhinosinusitis, including an impaired sense of smell. Despite probable effects on nutrition and overall health, CF-rhinosinusitis is little understood: CF-associated smelling deficiencies reported in literature vary between 12 and 71 %. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Cystic fibrosis (CF) provides another prominent example of a genetic mutation involving a specific TCNIC that classically results in CRS through abnormal mucociliary clearance. Although CF pathophysiology involves mutations of a transmembrane chloride ion transporter, CF patients, whose nasal liquid also consists of increased potassium concentrations, often report olfactory loss . In patients with these single‐gene defects, the dysfunctional ionic regulation within the upper and lower airways certainly extends to the olfactory cleft and increases the likelihood of olfactory impairment as a part of CRS symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis (CF) provides another prominent example of a genetic mutation involving a specific TCNIC that classically results in CRS through abnormal mucociliary clearance. Although CF pathophysiology involves mutations of a transmembrane chloride ion transporter, CF patients, whose nasal liquid also consists of increased potassium concentrations, often report olfactory loss . In patients with these single‐gene defects, the dysfunctional ionic regulation within the upper and lower airways certainly extends to the olfactory cleft and increases the likelihood of olfactory impairment as a part of CRS symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Data were excluded from final analyses if study participants failed to complete preoperative study evaluations as well as postoperative olfactory evaluations at 6 months, 12 months, and 18 months. Additionally, participants with either ciliary dyskinesia and/or corticosteroid dependent conditions were excluded from final analyses due to variations in global health, differential treatment considerations surrounding standard of care, and potential confounding of olfactory status …”
Section: Methodsmentioning
confidence: 99%
“…84 When administered via nebulized inhalation, the major advantage of this medication rests in its ability to reduce mucus viscosity by cleaving extracellular, long-chain DNA that accumulates in CF airways as a result of extensive neutrophil degradation. 60,85 In CF patients over age 5, dornase alfa has demonstrated significantly improved lung function as measured by forced expiratory volume in one second (FEV1) 86 , as well as decreased incidence of pulmonary exacerbations. 85,86 Moreover, bronchial inhalation of dornase alfa has been shown to reduce the annual rate of pulmonary deterioration in a number of trials.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
“…60,85 In CF patients over age 5, dornase alfa has demonstrated significantly improved lung function as measured by forced expiratory volume in one second (FEV1) 86 , as well as decreased incidence of pulmonary exacerbations. 85,86 Moreover, bronchial inhalation of dornase alfa has been shown to reduce the annual rate of pulmonary deterioration in a number of trials. 8691 A recent double-blind, placebo-controlled cross-over trial concluded that vibrating sinonasal inhalation of dornase alfa results in symptom and QOL improvement in patients with CF-related CRS.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%